2022
DOI: 10.1186/s12889-022-12620-3
|View full text |Cite
|
Sign up to set email alerts
|

Fatal drowning statistics from the Netherlands – an example of an aggregated demographic profile

Abstract: Introduction Incompleteness of fatal drowning statistics is a familiar problem impeding public health measures. Part of the problem may be that only data on accidental drowning are used and not the full potential of accessible data. Methods This study combines cause-of-death certificates and public prosecutor’s court documents between 1998 and 2017 to obtain an aggregated profile. Data are also used as a basis for a trend analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…Patients' demographic information and the seasonal distribution of drowning corresponded to other studies. (29,(32)(33)(34)(35)(36) This study reported an incidence of 1% drowning-related OHCA out of all OHCA, similar to that in Sweden. (37) This study con rmed a greater 30-day survival following drowning-related OHCA compared to OHCA from other causes found in other studies.…”
Section: Results Compared To the Existing Literaturementioning
confidence: 54%
“…Patients' demographic information and the seasonal distribution of drowning corresponded to other studies. (29,(32)(33)(34)(35)(36) This study reported an incidence of 1% drowning-related OHCA out of all OHCA, similar to that in Sweden. (37) This study con rmed a greater 30-day survival following drowning-related OHCA compared to OHCA from other causes found in other studies.…”
Section: Results Compared To the Existing Literaturementioning
confidence: 54%
“…Accessibility to highly lethal means for suicide is a key factor for determining suicide rates. For example, suicides by using guns is common in gun-carrying nations [ 172 , 173 ], carbon monoxide self-poisoning has become common in East Asian countries where charcoal is available over the counter [ 174 , 175 ], and drowning is specific to nations like Netherlands with many bodies of water [ 176 ] [ 177 ]. Two recent review articles on suicide in Pakistan [ 18 ][ 20 ] show poisoning to be the second most common mode of suicides [ 19 ] and the agents to be specific to regions where they are easily accessible [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 In the Netherlands, there are approximately 275 fatal drownings per year, with a rising trend observed in recent years. 2 The mortality rate associated with prolonged submersion (≥15–25 min) in drowning is high. 3 Clinical studies have demonstrated the benefits of extracorporeal cardiopulmonary resuscitation (ECPR) in cases of out-of-hospital cardiac arrest (OHCA), over standard advanced cardiac life support (ACLS) in selected patients, as ECPR facilitates immediate hemodynamic and respiratory stabilization of patients experiencing refractory cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%